PENGARUH NILAI OKTAN TERHADAP UNJUK KERJA MOTOR BENSIN DAN KONSUMSI BAHAN BAKAR DENGAN BUSI-KOIL STANDAR-RACING - Putra, Riki candra (ROTASI, 2020)
Many vehicle users considered that a higher octane number and the used of a racing ignition system could make the vehicle's performance better, but we need to looked more carefully by conducted experiments on dynamometers and motorbikes using variations in the octane number and standard coil spark plugs and racing. Experiments were carried out on 3 types of fuel with octane number values of 88, 90 and 92. The highest power value was obtained in octane number testing 92 with a racing coil spark plug of 6,753 kilo watts at rotating speed 7762.6  and the highest torque value occured in the octane number 92 with spark plug racing coil at 9,072 newton meters. The lowest maximum power value occured at 92 octane number with standard spark plugs of 6,601 kilo watts at rotating speed 7725 and the lowest maximum torque at 88 octane numbers with standard coil plugs is 8,914 newton meters at rotating speed 4584.8. The highest specific fuel consumption value at octane number 92 with spark plug racing coil at rotating speed 4000 is 0.116 Kg/kW.hour and the lowest specific fuel consumption value is at octane number 90 with spark plug standard coil at rotating speed 5000 is 0.08 Kg/kW.hour, and after testing the hypothesis with the independent T method with SPSS on rotation 2500 to 7500, it is concluding that the difference in power and torque values for each octane number and the use of standard and racing spark plugs does not show significant differences.